2012
DOI: 10.1159/000335468
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Daily Consumption of Probiotic Yogurt on Oxidative Stress in Pregnant Women: A Randomized Controlled Clinical Trial

Abstract: Background: Due to the enhanced oxygen requirement of the mitochondria-rich placenta primarily during the third trimester, pregnancy is associated with elevated levels of oxidative stress. This study was designed to determine the effects of daily consumption of probiotic yogurt on oxidative stress among Iranian pregnant women. Methods: This randomized single-blind controlled clinical trial was performed among 70 pregnant women, singleton primigravida, aged 18-30 in their third trimester. Subjects were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 101 publications
1
44
0
Order By: Relevance
“…Such findings have also been reached with the consumption of L. fermentum ME-3 [52] and multispecies probiotics in rats [53]. However, in our previous study in pregnant women [54], consumption of probiotic yogurt containing two strains of L. acidophilus LA5 and B. animalis BB12 did not lead to a significant effect on GSH compared to conventional yogurt. The difference in findings might be explained by differences in the studied populations.…”
Section: Discussionmentioning
confidence: 58%
“…Such findings have also been reached with the consumption of L. fermentum ME-3 [52] and multispecies probiotics in rats [53]. However, in our previous study in pregnant women [54], consumption of probiotic yogurt containing two strains of L. acidophilus LA5 and B. animalis BB12 did not lead to a significant effect on GSH compared to conventional yogurt. The difference in findings might be explained by differences in the studied populations.…”
Section: Discussionmentioning
confidence: 58%
“…Nine weeks of using probiotic yogurt increased plasma glutathione and erythrocyte glutathione reductase (GR), but did not significantly affect other oxidative stress indices in pregnant women. The positive results obtained in this study were attributed to up-regulation of antioxidant enzymes and reduction of inflammatory cytokines (which produce oxygen radicals and increase oxidative stress) [41]. Mann-Whitney U test.…”
Section: Discussionmentioning
confidence: 63%
“…The effect of probiotics on oxidative stress has previously been evaluated in humans (Asemi et al 2012;Ejtahed et al 2011Ejtahed et al , 2012) and animal models (Yadav et al 2007;Toral et al 2014). To the best of our knowledge, this study is the first study assessing the effect of probiotics soy milk on mitochondrial DNA lesion among diabetic patients.…”
Section: Discussionmentioning
confidence: 92%
“…To the best of our knowledge, this study is the first study assessing the effect of probiotics soy milk on mitochondrial DNA lesion among diabetic patients. In a study by Asemi et al (2012), probiotic yogurt consumption for 9 weeks decreased the plasma concentration of 8-oxo-G among pregnant women. Epp Songisepp et al (2005) indicated that probiotic Lactobacillus fermentum ME-3 caused Fig.…”
Section: Discussionmentioning
confidence: 96%